Nature of deviations from the regularities of three-particle recombination in dense plasma - Zhovtyansky, V.A. (Problems of Atomic Science and Technology, 2022)
An explanation is proposed for the phenomenon of deviations from the functional laws of three-particle recombination in dense electric arc plasma of argon at an initial electron density of ∼ 10¹⁶ cm⁻³. Experimental data, which are the basis of the work, were obtained by spectral and probe methods during the study of plasma decay of a micro-second pulse electric arc in argon 6 μs at an initial pressure of 70…700 Pa and a discharge current amplitude of 6 kA. Theoretical estimates show that the reason of the observed effects is the self-absorption of resonant spectral lines of argon, which significantly limits the recombination flow of electrons in the energy structure of atoms. Запропоновано пояснення явища відхилень від закономірностей трьохчастинкової рекомбінації в щільній плазмі аргону при початковій концентрації електронів ∼ 10¹⁶ см⁻³. Експериментальні дані, які покладені в основу роботи, отримані спектральним та зондовим методами при дослідженні розпаду плазми імпульсної електричної дуги в аргоні тривалістю 6 мкс при початковому тиску 70…700 Па та амплітуді розрядного струму 6 кА. Теоретичні оцінки показують, що причиною спостережуваних ефектів є самопоглинання резонансних спектральних ліній аргону, що істотно обмежує рекомбінаційний потік електронів у енергетичній структурі атомів.